’Pêra’ orange coating with whey protein concentrate film associated to plasticizers - Alleoni, Ana Cláudia Carraro; Jacomino, Angelo Pedro; Rosa, Alexandra Soares (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the effect of whey protein coating plasticized with glycerol and sorbitol in 'Pêra' oranges. Fruits were washed and sanitized, according to trade pattern, and then coated. Whey protein coatings was not effective in avoiding oranges weight reduction, independently of plasticizing. After 11 days of storage, the oranges coated with 6% protein and 6% glycerol, and with 4% protein and 8% sorbitol, lost less weight than other treatments. Coating did not modify physico-chemical characteristics of the oranges.